In Defense of the Asymmetric Convergence Model of Public Justification: A Reply to Boettcher - Vallier, Kevin (Ethical theory and moral practice, 2016)
This piece defends the asymmetric convergence model of public justification in response to James Boettchers critique. I maintain both that Boettchers critique of asymmetric convergence fails and that his alternative view, Weak Public Justification, faces a number of serious challenges.